Radiation Induces Pulmonary Fibrosis by Promoting the Fibrogenic Differentiation of Alveolar Stem Cells - Lu-Kai Wang; Tsai-Jung Wu; Ji-Hong Hong; Fang-Hsin Chen; John Yu; Chun-Chieh Wang (Stem Cells International)
The lung is a radiosensitive organ, which imposes limits on the therapeutic dose in thoracic radiotherapy. Irradiated alveolar epithelial cells promote radiation-related pneumonitis and fibrosis. However, the role of lung stem cells (LSCs) in the development of radiation-induced lung injury is still unclear. In this study, we found that both LSCs and LSC-derived type II alveolar epithelial cells (AECII) can repair radiation-induced DNA double-strand breaks, but the irradiated LSCs underwent growth arrest and cell differentiation faster than the irradiated AECII cells. Moreover, radiation drove LSCs to fibrosis as shown with the elevated levels of markers for epithelial-mesenchymal transition and myofibroblast (α-smooth muscle actin (α-SMA)) differentiation in in vitro and ex vivo studies. Increased gene expressions of connective tissue growth factor and α-SMA were found in both irradiated LSCs and alveolar cells, suggesting that radiation could induce the fibrogenic differentiation of LSCs. Irradiated LSCs showed an increase in the expression of surfactant protein C (SP-C), the AECII cell marker, and α-SMA, and irradiated AECII cells expressed SP-C and α-SMA. These results indicated that radiation induced LSCs to differentiate into myofibroblasts and AECII cells; then, AECII cells differentiated further into either myofibroblasts or type I alveolar epithelial cells (AECI). In conclusion, our results revealed that LSCs are sensitive to radiation-induced cell damage and may be involved in radiation-induced lung fibrosis.